Proteomic Modification by Nitric Oxide - Bian Ka; Ke Yan; Kamisaki Yoshinori; Murad Ferid (Elsevier, 2006)
Abstract.: The role of nitric oxide (NO) in cellular signaling has become one of the most rapidly growing areas in biology during the past two decades. As a gas and free radical with an unshared electron, nitric oxide participates in various biological processes. The interaction between NO and proteins may be roughly divided into two categories. In many instances, NO mediates its biological effects by activating guanylyl cyclase and elevates intracellular cyclic GMP synthesis from GTP. However, the list of cGMP-independent effects of NO is also growing at a rapid rate. In this review, the importance and relevance of nitrotyrosine formation are stressed. The utilization of intact cell cultures, tissues, and cell-free preparations along with the use of pharmacological, biochemical, and molecular biological approaches to characterize, purify, and reconstitute these NO regulatory pathways could lead to the development of new therapies for various pathological conditions that are characterized by unbalanced production of NO. Keywords:: nitric oxide, inducible nitric oxide synthase (iNOS, NOS-2), nitrotyrosine, peroxidase, hemin